Interaksi Sosial Dalam Mewujudkan Kasih Persaudaraan Antar Mahasiswa Asrama Perempuan Fakultas Teologi UKIT - Rondonuwu, Tezalonika Milkha; Ratag, Linda Patricia (Educatio Christi, 2024)
Love plays a role in realizing brotherhood in the life of boarding students in the Faculty of Theology, Tomohon Christian University of Indonesia, especially in the Women's Dormitory. Service involves Social Interaction so that it is hoped that through that interaction love can be emitted and become the identity of students of the Faculty of Theology UKIT. In reality. Many students forget God's love for each person so that they also do not succeed in practicing that love in their daily lives. The reality in boarding life is that many people no longer respect each other, there are often hypocritical attitudes that ultimately make misunderstandings between boarding communities and worse, it can end up being provocative. So that teaching about Fraternal Love in Social Interaction is very important to build the character of students to become better servants and have integrity in the future.